Islam and the Secular State in Indonesia - Assyaukanie, Luthfi (ISEAS Publishing, 2009)
This is, in itself, a notable advance, taking us beyond the efforts at categorisation and typology-building based on socio-economic categories that have characterized the field since Geertz’s seminal work in the early and mid-1950s. It discusses such matters as the relationship of Islamism to democracy, the role of the state in sustaining religious belief and practice, and the problem of secularism. This is a confident, controversial, and passionately argued piece of work. It sheds new and powerful light on the nature, depth and trajectory of mainstream Islamic thinking in Indonesia." - Professor Robert E. Elson, University of Queesland, Australia